2003
DOI: 10.1046/j.1365-2141.2003.04146.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of factor VIIa generation and prothrombin activation by treatment with enoxaparin in patients with unstable angina*

Abstract: Summary. Factor VIIa (FVIIa) and thrombin generation occur in patients suffering an acute coronary event. We studied the effect of treatment with enoxaparin on FVIIa and prothrombin activation in patients with unstable angina. Anti-Xa activity, FVIIa, FVII coagulant activity (FVII:C) and FVII antigen (FVII:Ag), free tissue factor pathway inhibitor (TFPI), and prothrombin fragments 1 + 2 (F 1+2 ) were measured in patients' plasma, over a 24-h treatment period with enoxaparin. All 14 patients recruited in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
(48 reference statements)
1
6
1
6
Order By: Relevance
“…Because both groups used the same assay to measure F1+2 as we did, we have no explanation for this difference 27,28 . In contrast, compared to other studies with the same assay, F1+2 levels we found are only slightly above those described in healthy controls 29 and considerably lower than F1+2 levels found in patients undergoing coronary artery bypass grafting during surgery 30 …”
Section: Discussioncontrasting
confidence: 50%
“…Because both groups used the same assay to measure F1+2 as we did, we have no explanation for this difference 27,28 . In contrast, compared to other studies with the same assay, F1+2 levels we found are only slightly above those described in healthy controls 29 and considerably lower than F1+2 levels found in patients undergoing coronary artery bypass grafting during surgery 30 …”
Section: Discussioncontrasting
confidence: 50%
“…LMW heparins furthermore inhibit the initiation of coagulation by mobilization of tissue factor pathway inhibitor from endothelial cells [24]. Short-term treatment with LMW heparins in unstable CAD has previously been shown to reduce coagulation activity with decreased levels of activated factor VII, prothrombin fragment 1 + 2 and D-dimer [14][15][16][17]. In concordance, the prolonged dalteparin treatment in the present study resulted in marked reduction of coagulation activity with significantly lower levels of all three coagulation markers, factor VIIa, prothrombin fragment 1 + 2 and D-dimer, up to 3 months after the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“…Although data specific to STEMI are lacking, the pharmacokinetic profile of subcutaneous enoxaparin appears to be similar in healthy individuals and those with unstable angina, with appropriate anticoagulation levels generally achieved 45 min to 60 min following administration (antifactor Xa greater than 0.5 U/mL) (15,16). The interval from enoxaparin administration until first balloon inflation exceeded these values in our index cases.…”
Section: Discussionmentioning
confidence: 85%